PENGARUH DOSIS DAN KONSENTRASI PUPUK HAYATI TERHADAP PERTUMBUHAN DAN HASIL TANAMAN KACANG HIJAU (Vigna radiata L.) VARIETAS VIMA-1 - Wibowo, Wisnu Aji; Darini, Maria Theresia; Pamungkas, Djoko Heru (Universitas Sarjanawiyata Tamansiswa, 2017)
The research aims to study the interaction, effectivness dosage and concentration of biofertilizer diversity, to growth and production of mungbean. This reasearch was conducted in Wedomartani, Special Region of Yogyakarta in Oktober to Desember 2015, altitude of 120 m above sea level, temperature 24-32o C, relative humidity (RH) 73-89%, C2 Climate and Annual rainfall + 2.000 mm. The type of soil used Regosol and Kambisol, pH 6-7. The research was arranged in RCBD (Random Complete Block Design) in two factorial with three replicaton. The first factor was Rhzobium sp.’ dosage, with two level were 7,5 gram, and 15 gram per kg seedling. The second factor was liquid biofertilizer’ concentration , with four level were 0 %, 2,5%, 5%, and 7,5 %. Growth observation variable were plant height, number of nodules, nodule weight, number of effective nodule, number of leaves, leaf area, fresh weight, dry weight, and the number of pods. Production observation variable were fresh pod weight, dry pod weight, the amount of fresh seeds per pod, pods weight per plot, 100 seeds weight, harvest index, and leaf area index. Statistical analysis conducted on all data observations using ANOVA (Analysis of Variance) at the significant level of 5% followed by DMRT (Duncan’s Multiple Range Test) at the significant level of 5%. The results showed the combination have interaction and effectivness in adding biofertilizer diversity in growth and production of mungbean. The best treatment dosage and concentration in growth and production was 7,5g/kg Rhizobium sp., and 7,5% liquid biofertilizer’ concentration